1996
DOI: 10.1074/jbc.271.27.16281
|View full text |Cite
|
Sign up to set email alerts
|

Control of Starch Composition and Structure through Substrate Supply in the Monocellular Alga

Abstract: In Chlamydomonas, as in higher plants, synthesis of ADP glucose catalyzed by ADP-glucose pyrophosphorylase is rate-limiting for the building of starch in the chloroplast. We have isolated disruptions of the STA1 ADP-glucose pyrophosphorylase structural gene that rendered the enzyme less responsive to the allosteric activator 3-phosphoglycerate. The structure and composition of the residual starch synthesized by all mutants of the STA1 locus is dramatically altered. The residual polysaccharide is shown to be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 34 publications
2
57
0
1
Order By: Relevance
“…Starch accumulation is severely affected in plants that are deficient in ADGase activity. This has been shown in Arabidopsis leaves (Lin et al, 1988a, b), maize endosperm (Weaver et al, 1972), pea cotyledons (Smith et al, 1989), Chlamydomonas (Van den Koornhuyse et al, 1996), and in tubers of potato plants expressing antisense constructs of an ADGase gene (Muller-Rober et al, 1992). The Arabidopsis adg2 mutant has only~5% ADGase activity but accumulates~40% of wild-type starch levels (Lin et al, 1988b).…”
Section: Introductionmentioning
confidence: 84%
“…Starch accumulation is severely affected in plants that are deficient in ADGase activity. This has been shown in Arabidopsis leaves (Lin et al, 1988a, b), maize endosperm (Weaver et al, 1972), pea cotyledons (Smith et al, 1989), Chlamydomonas (Van den Koornhuyse et al, 1996), and in tubers of potato plants expressing antisense constructs of an ADGase gene (Muller-Rober et al, 1992). The Arabidopsis adg2 mutant has only~5% ADGase activity but accumulates~40% of wild-type starch levels (Lin et al, 1988b).…”
Section: Introductionmentioning
confidence: 84%
“…Thus, amylose may be more readily synthesized in sex4 granules than in wildtype or sex1 granules. However, other factors such as the supply of substrates are also known to influence amylose synthesis (Van den Koornhuyse et al, 1996;Clarke et al, 1999) and may also contribute to the observed differences.…”
Section: Amylose Content Of Leaf Starchmentioning
confidence: 99%
“…First, changes in the concentration of ADP-Glc can affect the relative activities of isoforms of starch synthase, and hence starch structure (Van den Koornhuyse et al, 1996;Clarke et al, 1999). GBSS has a much lower affinity for ADPGlc than soluble isoforms, and there appear to be differences between the soluble isoforms in their affinities for this substrate (Clarke et al, 1999;Edwards et al, 1999a;Lloyd et al, 1999a).…”
Section: Plants With Alterations In the Pattern Of Suc Supply To The mentioning
confidence: 99%